NOTE: USE OF PARAAMINOBENZOIC ACID TO IMPROVE YIELD OF SILKWORM (Bombyx mori L.) - Pai, IK; Hedge, SN; Krishnamurthy, NB (Annals of Tropical Research, 1987)
Paraaminobenzoic acid (PABA) at 50, 100, 200 and 400 ppm concentrations were administered to third instar larvae of silkworm (Bombyx mori L.) by leaf dip method. Results showed marked improvement of the silk percentage at low concentrations of 50-100 ppm. The use of appropriate PABA concentrations in commercial silkworm rearing is thus recommended.